Model Arsitektur Percabangan Beberapa Pohon di Taman Nasional Alas Purwo - Ekowati, Gustini; Indriyani, Serafinah; Azrianingsih, Rodiyati (Biotropika: Journal of Tropical Biology, 2017)
TheÂ Alas Purwo National Park (APNP) has been designated as a world reserved biosphere by UNESCO. Reserved biosphere is an area consisting of the original ecosystem, unique ecosystems, or ecosystems that have degraded their entire natural elements; therefore, this biosphere is protected and preserved for research and education. To support the protection and preservation efforts, it is important to conduct a basic research for empowering the plant species. This study aimed to characterize the architectural model based on the branching tree and to make a key determination or identification of tree species in the APNP. Exploration of APNP area was conducted using the survey methods; it had been done by passing through the triangulated, going to the bridge Sunglon Ombo until Pancur, then rotating to the cave Istana, the lodge of Sadengan, then going back to the triangulated. The architectural model and the type of branch of trees in APNP were observed. They were stratified by 23 of the known architectural models. The data was descriptively analyzed then the key determination was made. The result showed 11 of tree architecture models consisted of Troll 14 types, Scarrone 4 types, Corner 4 types, Leeuwenberg 3 types, Aubreville 3 types, Mc Clure 3 types, Rauh 5 types, Masart 2 types, Holtum 1 type, Prevost 1 type, and Koriba 1 type. Furthermore, the 11 plants as the examples of the architectural model were described, completed with photos, and notes on endemic species of APNP. The identification key for multiple branching trees also was added depending on the model.